Application of plant protection biological product via pulsed intra-soil discrete methodology. Issue 1 (1st October 2022) - Chaplygin, V; Budynkov, N; Glinushkin, A; Mikhaleva, S; Proskurin, A; Kozyrev, S; Kalinitchenko, V; Minkina, T; Chernenko, V; Mandzhieva, S; Sushkova, S; Barakhov, A; et al.
Abstract: Hardly decomposable aboveground and underground plant residues are a substrate for the Fusarium graminearum, F. moniliforme and other dangerous infections of subsequent crops in the crop rotation. For the period 2014-2020, an infection of grain with F. moniliforme increased in the Kursk region by 2.3 times; in Volgograd region by 3.7 times; in Rostov region by 8.7 times; and in the Stavropol Territory by 5.4 times. After treatment of plant residues of corn with biological preparation-sanator, a rhizoctonia disappeared from the winter wheat agrophytocenosis, and an occurrence of the F. moniliforme decreased by 2.5 times; a frequency of occurrence of pathogenic fungi F. moniliforme and F. avenaceum on the aerial parts of a plant was 20%, and on the plant residues 10% or less. A microbial colonization of the underground residues of sunflower and corn plants by F. moniliforme after harvesting was up to 30% for three years. Intra-soil pulse continuous-discrete robotic system for application of a biological plant protection product has been developed to increase an impact of biological plant protection product on phytopathogen into the plant residue and topsoil. The method provides priority plant protection from harmful biological objects, improving soil health, increasing plant productivity and product quality.